Study on the association of wall shear stress and vessel structural stress with atherosclerosis: An experimental animal study. (March 2021) - Teng, Zhongzhao; Wang, Shuo; Tokgoz, Aziz; Taviani, Valentina; Bird, Joseph; Sadat, Umar; Huang, Yuan; Patterson, Andrew J.; Figg, Nichola; Graves, Martin J.; Gillard, Jonathan H.
Abstract: Background and aims: Artery is subject to wall shear stress (WSS) and vessel structural stress (VSS) simultaneously. This study is designed to explore the role of VSS in development of atherosclerosis. Methods: Silastic collars were deployed on the carotid to create two constrictions on 13 rabbits for a distinct mechanical environment at the constriction. MRI was performed to visualize arteries' configuration. Animals with high fat (n = 9; Model-group) and normal diet (n = 4; Control-group) were sacrificed after 16 weeks. 3D fluid-structure interaction analysis was performed to quantify WSS and VSS simultaneously. Results: Twenty plaques were found in Model-group and 3 in Control-group. In Model-group, 8 plaques located proximally to the first constriction (Region-1, close to the heart) and 7 distally to the second (Region-2, close to the head) and 5 plaques were found on the contralateral side of 3 rabbits. Plaques at Region-1 tended to be bigger than those at Region-2 and the macrophage density at these locations was comparable. Minimum time-averaged WSS (TAWSS) in Region-1 was significantly higher than that in Region-2, and both maximum oscillatory shear index (OSI) and particle relative residence time (RRT) were significantly lower. Peak and mean VSS in Region-1 were significantly higher than those in Region-2. Correlation analyses indicated that low TAWSS, high OSI and RRT were only associated with plaque in Region-2, while lesions in Region-1 were only associated with high VSS. Moreover, only VSS was associated with wall thickness of plaque-free regions in both regions. Conclusions: VSS might contribute to the initialization and development of atherosclerosis solely or in combination with WSS. Graphical abstract: Image 1 Highlights: Distinct mechanical environment can be created by two constrictions along the carotid artery to induce atherosclerosis. Low wall shear stress (WSS), high oscillatory shear index (OSI) and long particle relative residence time (RRT) were only associated with atherosclerosis in the constriction close to the head. High vessel structural stress (VSS) was associated with atherosclerosis in the constriction close to the heart. High VSS was associated with the density of CD68 and the wall thickness around both constrictions.